Rural-urban disparities in basic sanitation access among households: a multivariable decomposition analysis of Ethiopian demographic and health survey 2019 - Keleb, Awoke; Daba, Chala; Endawkie, Abel; Asmare, Lakew; Bayou, Fekade Demeke; Abeje, Eyob Tilahun; Ayres, Aznamariam; Mohammed, Anissa; Kebede, Natnael; Abera, Kaleab Mesfin; Mekonen, Asnakew Molla; Gebeyehu, Endalkachew Mesfin; et al. (Frontiers in Public Health, 2024)
Introduction Disparities in access to basic sanitation services between rural and urban households pose significant challenges to public health and human development. Understanding the determinants contributing to this gap is vital for advancing the Sustainable Development Goals (SDGs) and improving environmental and public health through evidence-based interventions. Objective This study aims to analyze and understand the disparities in access to basic sanitation services between rural and urban households in Ethiopia. Methods This study analyzed a sample of 8,663 weighted households, collected using stratified sampling techniques, utilizing the data from the 2019 Ethiopian Demographic and Health Survey (EDHS). The primary outcome was basic sanitation access, defined as access to flush or pour-flush systems, septic tanks, pit latrines, or composting toilets. A multivariable decomposition analysis was conducted to identify factors contributing to rural–urban disparities. Statistically significant variables were determined at a p-value of <0.05 with a 95% confidence interval. Results The weighted proportion of basic sanitation access in Ethiopia was 13.78% (95% CI, 12.67–14.96), with significant disparities between rural (6.02%) and urban (27.15%) residents. Endowment factors accounted for 78.9% of this disparity, while behavioral coefficients contributed 22.1%. If the characteristics of respondents in rural and urban households had been similar, significant factors that would have narrowed the gap included the age of the household head (15–35 years), the absence of under-five children, smaller family size, and the attainment of secondary education, reducing the gap by 1.83, 2.07, 5.08, and 3.25%, respectively. Conversely, illiteracy and primary education levels widened the gap between rural and urban access to basic sanitation services by 16.85 and 0.23%, respectively. Additional factors exacerbating the rural–urban disparity included poverty (which widened the gap by 58.71%), residence in pastoralist regions (which widened the gap by 10.10%) or agrarian regions (which widened the gap by 7.03%), and access to water sources located more than 30 min away (which widened the gap by 7.91%). Conclusion Significant disparities in access to basic sanitation services exist between rural and urban households in Ethiopia. Key factors contributing to these disparities include the age of the household head, education level, family size, region of residence, and water source proximity. Addressing these factors is essential for improving sanitation access and achieving the Sustainable Development Goals (SDGs).